WEWENANG KEPOLISIAN DALAM PROSES PENYIDIKAN TINDAK PIDANA KORUPSI DI POLDA BALI - Widiasa, I Made; Rai Setiabudhi, I Ketut; Wirasila, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2013)
This study examines the Police Authority in Corruption Investigation Process. There are two issues that were examined. First, what is the authority of the Police in the investigation of the handling of corruption. Second, whether the factors that support and hinder the police investigation against corruption. This research was conducted using the method of empirical legal research. Thus the legal data obtained in two ways, namely primary data obtained directly in the field and secondary data obtained through library research. The following results that the Police have the authority to investigate corruption by Act 2 of 2002 on the Indonesian National Police, Law No.31 of 1999 on Eradication of Corruption, and Law No.30 of 2002 on Corruption Eradication Commission , all of them referring to the criminal Procedure Code as a basis for criminal law. Blocking is done in the process of investigation is used as an investigator and foreclosure prevention efforts can be used as a repressive efforts in saving the proceeds of corruption. The factors that influence the investigation of the factorssupporting the legal factors inhibiting factor is the factor of infrastructure and lawenforcement factors.
Keywords: Authority Police, Investigation, Crime of corruption, and process investigation of corruption